Management of Divergence Excess Intermittent Exotropia. - Flax, Nathan (Optometry & Visual Performance, 2018)
A method of treating divergence excess intermittent exotropia which differs from standard orthoptics is presented. Training is not done at the objective angle; ARC is ignored; diplopia awareness is not cultivated; stereoscopic targets are introduced before flat fusion or simultaneous perception targets; little emphasis is placed on developing base-out prism vergence ranges; monocular skills and accommodative facility are developed; and plus adds are utilized. The rationale for this approach is developed.